Determination of an appropriate projection system for forest areas in Turkey - Yildirim, Faruk; Kadi, Fatih; Kurtipek, Adem (Geodesy and Cartography, 2020)
Geometrical surfaces such as sphere and ellipsoid are considered as reference surfaces since there is no geometric shape that perfectly represents the earth when translating the earth into a map plane. Hence, on 3D reference surfaces, it is almost impossible to perfectly preserve the angle, direction and area properties and transfer them to a map plane without any deformations. The scaled topographic maps produced in our country under provision of map production regulations are conformal projections that do not preserve area properties but angle and shape properties. Area values calculated by projection coordinates cannot be considered the exact area values therefore, an area reduction is needed. Area values calculated by ignoring this situation in GIS based software do not represent the accurate area values on reference surfaces. The aim of this study is to determine the best area preserving projection for GIS applications in which area values are important. In this study, the real area values of 25 large-extent forest parcels are determined by employing the Danielsen method with geographical coordinates on ellipsoid surface. These parcels are also calculated by using the area-preserving projections available in ArcGIS software and are compared to their real area values.